The Origin of LAMOST J1109+7459 - Yazan Khrais; Nour Aldein Almusleh
We report a comprehensive Chemo-dynamical analysis of LAMOST J1109+0754, a relatively bright (V = 12.8), extremely metal-poor ([Fe/H] = -3:17), and prograde (Jф and Vф > 0) star, with a strong r-process enhancement ([Eu/Fe] = +0.94 ± 0.12, [Ba/Fe] = -0.52 ± 0.15). 31 chemical abundances (from Lithium to Thorium) were derived. We suggest a possible progenitor with stellar mass of 13.4-29.5Mo. We argue that J1109+0754 is representative of the main r-process component due to the well agreement with the scaled-solar r-process component. We analyze the orbital history of this star in a time-varying Galactic potential, based on a Milky-Way analogue model extracted from Illustris-TNG simulations. Using this model, we carry out a statistical estimation of the phase-space coordinates of J1109+0754 at a young cosmic age. Collectively, the calculated motions, the derived chemistry, and the results from the cosmological simulations suggest that LAMOST J1109+0754 most likely formed in a low-mass dwarf galaxy, and belongs to the Galactic outer-halo population.
Keywords: Astronomy